Can deunionization lead to international outsourcing? - Kjell Erik Lommerud; Frode Meland; Odd Rune Straume (Center for Economic Studies and ifo Institute (CESifo), 2005)
We analyze unionized firms? incentives to outsource intermediate goods production to foreign (low-cost) subcontractors. Such outsourcing leads to increased wages for the remaining inhouse production. We find that stronger unions, which imply higher domestic wages, reduce incentives for international outsourcing. Though somewhat surprising, this result provides a theoretical reconciliation of the empirically observed trends of deunionization and increased international outsourcing in many countries. We further show that globalization - interpreted as either market integration or increased product market competition - will increase incentives for international outsourcing.
Keywords: L24; J51; F16; 330; international outsourcing; deunionization; globalization; Outsourcing; Gewerkschaftlicher Organisationsgrad; Globalisierung; Theorie